Comparative Study on the Performance of Three-Blade and Four-Blade Archimedes Wind Turbines at Low Wind Speeds Using Ansys Simulation - Faroja, Anas; Arifin, Fatahul; RS, Carlos (International Journal of Mechanics, Energy Engineering and Applied Science (IJMEAS), 2026)
The Archimedes wind turbine is a promising technology for renewable energy applications in low wind speed conditions, yet the optimization of the blade geometry still requires a comprehensive investigation. This study aims to analyze the effect of variations in the number of blades (three and four) and pitch angles (50°, 55°, 60°, and 65°) on the aerodynamic performance of Archimedes wind turbines using the ANSYS 2024 R1 Computational Fluid Dynamics (CFD) simulation. The research methodology applied the SST turbulence model k-ω with a constant Tip Speed Ratio (TSR) at a value of 1 to isolate the influence of geometric parameters on the coefficient of power (Cp). The simulation was carried out with a residual convergence criterion of 0.001 throughout 1000 iterations until a stable solution was reached. The results of the analysis showed that a four-blade configuration with a pitch angle of 65° resulted in an optimal Cp of 0.2027, representing an 85.6% performance improvement over the three-blade configuration of 50° (Cp = 0.1092). Velocity and pressure contour visualization revealed that the four blades demonstrated superior attachment flow, a more even distribution of pressure differential, and an organized wake structure that minimized energy dissipation. The study's conclusions identified a four-blade configuration at a pitch angle range of 60-65° as the optimal design for Archimedes wind turbine applications in low wind speed conditions, making a significant contribution to the development of renewable energy technologies for urban and tropical regions.